2002
DOI: 10.1038/sj.ejcn.1601472
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitation of major carotenoids in selected components of the Mediterranean diet: green leafy vegetables, figs and olive oil

Abstract: Objective: To characterize the carotenoid content of selected components of the Mediterranean diet commonly eaten by Greek migrants to Melbourne, a population group maintaining a traditional dietary regimen, and who exhibit relatively high circulating carotenoid concentrations and low cardiovascular disease mortality. Design and specimens: Opportunistic sampling of wild (sow thistle, amaranth, purslane and dandelion, collected from roadsides and home gardens) and commercially available (chicory, endive) green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 17 publications
5
51
1
Order By: Relevance
“…35 Wild-growing green leafy vegetables are generally richer sources of various micronutrients than exotic or commercially produced leafy vegetables. [35][36][37] This study confirms the general belief that information on African leafy vegetables is passed down over generations. There are, however, indications from the KZN sites that clinics and radio are also an important source of information on imifino, pointing to these as potentially worthwhile communication channels for nutritional promotion of these leaves.…”
Section: Discussionsupporting
confidence: 75%
“…35 Wild-growing green leafy vegetables are generally richer sources of various micronutrients than exotic or commercially produced leafy vegetables. [35][36][37] This study confirms the general belief that information on African leafy vegetables is passed down over generations. There are, however, indications from the KZN sites that clinics and radio are also an important source of information on imifino, pointing to these as potentially worthwhile communication channels for nutritional promotion of these leaves.…”
Section: Discussionsupporting
confidence: 75%
“…These carotenoids are of importance in human health ( 17 ). The leafy vegetable species studied were rich in ␤ -carotene and lutein as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown a significant correlation between habitual vegetable and fruit intake in plasma carotenoid concentrations. The use of olive oil in food preparation aids absorption of lipid-soluble compounds such as carotenoids, particularly those less polar, as well as being an important source of α-tocopherol in itself [11] .…”
Section: Discussionmentioning
confidence: 99%
“…A healthful diet has long been considered essential in prevention, or reducing the risk of developing these diseases. Vegetables are a major source of carotenoids and because of their antioxidant properties, these compounds are thought to contribute to the beneficial effects of vegetable consumption [11] .…”
Section: Introductionmentioning
confidence: 99%